STRATEGI AKSELERASI PENINGKATAN PENDAPATAN PETANI JAMBU METE DI SULAWESI TENGGARA - JULIAN WITJAKSONO; AHMAD SULLE; SUBAEDAH RUKU (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
The cashew nuts production in Southeast Sulawesi has been showed the indicated todecreasing productivity and production fluctuation for ten years between 1995 until 2004. Thecashew farming in Southeast Sulawesi especially in Muna district such as center productionshowed the low income on household farmers. The review of this paper showed the actualcondition with the cashew farmers in their villages in Muna district that there were manyfactors determinants, i.e. the availability capital, input production, cashew trees condition,land condition, technology, managerial, market institutions, farming instructors and financialinstitution. This paper has the objectives main to improving the cashew farmer’s conditionneeded to increase their income on household farmers. The strategy for improving the abovecondition i.e. integration farming system between animals and crops especially in their fieldof cashew trees, past harvesting, quality, and market and pattern crops for the landoptimization after the rehabilitation cashew trees. The five above condition is the crucialdeterminants as the good strategy hope to improving their condition especially to increase theproductivity and farmers income on household farming